Pengaruh Sharia Financial Literacy Dan Investment Risk Terhadap Keputusan Investasi Emas Di Pegadaian Syariah Dengan Pendapatan Sebagai Variabel Moderating - Anggraini, Nadea Silvi; Cahyono, Edi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study aims to understand and analyze the influence of sharia financial literacy and investment risk on gold investment decisions at Pegadaian Syariah, with income as a moderating variable. This research employs a quantitative method using primary data obtained from questionnaires, which were then analyzed using SPSS software. The sample consists of 104 respondents from the Jepara community who invest in Pegadaian Syariah Jepara. The data analysis reveals that: (1) Sharia financial literacy has a positive and significant effect on gold investment decisions; (2) Investment risk does not affect gold investment decisions; (3) Income does not affect gold investment decisions; (4) Income does not moderate the influence of sharia financial literacy on gold investment decisions; and (5) Income does not moderate the influence of investment risk on gold investment decisions.